Cidade transcendental: uma análise historiográfica da obra "Assombrações do Recife velho", de Gilberto Freyre. - Alves Neto, Braz Pereira (2019)
Recife, capital of the contradictory, beautiful and cruel. A city in which the population, at times, demonstrates a degree of irreverence in dealing with ever yday life and profound reverence to its mysteries. Their “coexistence with ghosts”, an intimate aspect of the city, with its changes and permanences, was noticed by writer Gilberto Freyre. This author, which in the 1920‟s -when he was director of the A Província newspaper – called for the investigation of stories about the “supernatural” and oriented their publication. In the passing years, he collected several testimonies of phantasmagorias coming from the distinct communities which lived together in Recife. In 1955, he published a collection of narratives entitled Assombrações do Recife Velho (Hauntings of Old Recife). In yore labeled by critics as a “lateral” or “parallel” work, “exotic”, today we can infer, taking history theorists as a basis, that the book presents itself as an interesting source of research. In this dissertation, we aim to analyze it under historiographic lenses. We take into consideration the importance of linking the story of the book with the one of its author and collaborators, as well as the city of Recife‟s. We highlight that the image composition, reception and longevity of the Assombrações do Recife Velho theme are also present in our analysis.